Growth Curve of Amazonian Manatee (Trichechus inunguis) in Captivity - Mendoza, Pierina [UNESP]; Velasquez, Javier; Sanchez, Juan; Davila, Leonardo; Loja, Darwin; Riveros, Rony [UNESP]; Vilchez, Carlos (European Assoc Aquatic Mammals, 2019)
The objective was to describe the growth curve for Amazonian manatees (Trichechus inunguis) raised in a captive facility in the Peruvian Amazon. We collected data on age (in months), body weight (BW; kg), and curved total length (CTL; cm) as biometric measurements of four rescued manatees (two males and two females). We used the Simple Gompertz equation to model the data and obtain a growth curve estimate. From the evaluated manatees, growth rates were estimated by sex: (1) for males, the growth rate was 0.11 kg/mo and 0.06 cm/mo, reaching an asymptotic BW of 100.06 kg and CTL of 196.31 cm; and (2) for females, the growth rate was 0.09 kg/mo and 0.06 cm/mo, with an asymptotic BW of 131.52 kg and CTL of 207.40 cm. The age at the maximum speed of weight and CTL growth for males was around 17.97 to 17.44 mo old, and 21.93 to 16.81 mo old for females. The Gompertz equation was a good mathematical model to describe the growth rate of the Amazonian manatee.
Keywords: Amazonian manatee; Trichechus inunguis; Gompertz function; growth modelling; maturity age